2007
DOI: 10.1016/s1063-4584(07)61648-3
|View full text |Cite
|
Sign up to set email alerts
|

12 Bone Marrow Lesions From Osteoarthritis Knees Are Characterized by Sclerotic Bone That Is Less Well Mineralized

Abstract: Morgan. "Bone marrow lesions from osteoarthritis knees are characterized by sclerotic bone that is less well mineralized" Arthritis Research & Therapy 11(1):R11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…While the exact etiology of BMLs remains unclear, multiple studies have shown a significant association between BMLs on MRI and the development of OA, which is thought to be related to increased remodeling activity. 18 19 20 21 An early study by Felson et al investigated the effects of BMLs on OA in 246 patients. After adjusting for limb alignment, they found the odds ratio of progression to OA in the presence of medial and lateral compartment (tibial and femoral) lesions was 5.6 and 2.8, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact etiology of BMLs remains unclear, multiple studies have shown a significant association between BMLs on MRI and the development of OA, which is thought to be related to increased remodeling activity. 18 19 20 21 An early study by Felson et al investigated the effects of BMLs on OA in 246 patients. After adjusting for limb alignment, they found the odds ratio of progression to OA in the presence of medial and lateral compartment (tibial and femoral) lesions was 5.6 and 2.8, respectively.…”
Section: Discussionmentioning
confidence: 99%